SAT0196 An assessment of impairment of productivity among SLE patients. (23rd January 2014) - Schneider, M.; Strand, V.; Nikaï, E.; Wood, R.; Smets, E.; Lobosco, S.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that predominantly affects women. SLE can affect both patients' ability to attend work and their productivity while at work. 1 In the 2010 Lupus European Online (LEO) survey, SLE patients reported high levels of impairment in work and activities outside work, and a high prevalence of fatigue. 2 Further insight into factors associated with work productivity impairment in SLE patients would be valuable. Objectives: To assess the impact of SLE on productivity at various disease severity levels. Methods: Data from five European countries (France, Germany, Italy, Spain, UK) and the US were extracted from the Adelphi Lupus Disease-Specific Programme 3, a 2010 cross-sectional survey completed by 161 physicians (156 rheumatologists, 5 nephrologists) and 456 SLE patients. Patients reported their productivity in the Work Productivity and Activity Impairment (WPAI-Lupus) questionnaire. WPAI has four domains: absenteeism (% time missed from work), presenteeism (% impairment due to SLE while working), overall work impairment (% overall work impairment due to health problems) and activity impairment (% impairment in regular daily activities other than paid work), higher numbers indicating greater impairment. Disease severity was physician-reported, based on overall perception of disease activity. Results: Patients were predominantly female (87.7%). Their mean age was 39.8 years, and 55.5% were employed. Impairment in each of the four WPAI domains (Table 1 ) was reported, with a similar negative effect on both regular daily activities (outside work) and work productivity (27.3% and 25.1%, respectively). Levels of impairment in the four WPAI domains were compared for three levels of disease activity: mild, moderate and severe (as defined by rheumatologists). Moderate and severe patients were grouped together because few patients were classified as severe (n=2–8 depending on the domain). In three of the four domains, greater disease severity was associated with greater productivity impairment. Impairment was greatest in the regular daily activities domain, where WPAI impairment increased from 21.41% to 40.73% for mild vs moderate/severe disease. Conclusions: The burden of SLE on productivity was considerable, with impairment across all WPAI domains. The most affected domain was regular daily activities. Increased disease activity was associated with greater productivity impairment in three domains. This analysis provides insight into the burden of SLE in Europe and the US. Further research is required to investigate the effect of other factors such as fatigue and pain on productivity in this population. References: Baker et al. Rheumatology (Oxford) 2009;48:281-4. Schneider et al. Presented at: Annual European Congress of Rheumatology 2011. Anderson et al. Curr Med Res Opin 2008;24:3063-72. Disclosure of Interest: M. Schneider Consultant for: UCB Pharma, V. Strand Consultant for: UCB Pharma, E. Nikaï Employee of: UCB Pharma, R. Wood Consultant for: UCB Pharma, E. Smets Employee of: UCB Pharma, S. Lobosco Consultant for: UCB Pharma